Description of pregnant women who participate in gymnastics - Arinta, Illa; Nuurjannah, Febri Annisaa; Dwijati, Indah; Cantika, Hilda (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Latar Belakang. Senam hamil merupakan salah satu kegiatan dalam pelayanan kesehatan pada masa kehamilan (prenatal care) dan senam hamil akan memberikan hasil kehamilan atau persalinan normal lebih baik dari pada ibu hamil yang tidak melakukan senam hamil. Ibu hamil yang melakukan senam hamil diharapkan dapat menjalani persalinan dengan lancar, dapat memanfaatkan kelebihan dan kemampuannya dengan sebaik-baiknya sehingga proses persalinan dapat berjalan relatif cepat dan nyeri berkurang. Metode Penelitian. Desain penelitian yang digunakan adalah kuantitatif dengan menggunakan pendekatan cross sectional, lokasi penelitian dilaksanakan di Puskesmas Cempaka Putih pada bulan Agustus 2018, dengan sampel ibu bersalin sebanyak 33 orang. Instrumen yang digunakan adalah register. Variabel yang digunakan adalah lamanya waktu persalinan. Hasil. Responden yang rutin mengikuti senam kala I persalinan sebanyak 69,7%, sedangkan ibu yang mengikuti senam kala I persalinan secara teratur sebanyak 30,3%. Terdapat hubungan yang signifikan antara senam dengan lamanya waktu persalinan. Kesimpulan. Hasil penelitian diketahui dari 33 ibu hamil yang mengikuti senam hamil secara rutin sebanyak 28 responden dengan presentase 14,76%, sedangkan yang tidak rutin mengikuti senam hamil sebanyak 5 responden dengan presentase 15,2%. Responden yang mengikuti senam rutin dengan lama persalinan lama sebanyak 69,7%, sedangkan ibu yang mengikuti senam rutin dengan lama persalinan cepat 30,3%. Ada hubungan yang signifikan antara senam dengan lama persalinan. Kata Kunci : Senam, Persalinan. ABSTRACT Background: Pregnancy gymnastics is one of the activities in health services during pregnancy (prenatal care) and pregnancy gymnastics will provide a better pregnancy or normal delivery product results than for pregnant women who do not do pregnancy exercises. Pregnant women who do pregnancy exercises are expected to be able to undergo labor smoothly, be able to make the best use of energy and abilities so that the delivery process can run relatively quickly and pain is reduced. Objective: this study is an Overview of Pregnant Women Who Participate in Pregnancy Gymnastics at the Cempaka Putih District Health Center in 2017. Research Method: Secondary data is by taking Register data, data on the number of pregnant women who participate in gymnastics with a sample of 184 respondents. data obtained from Medical Records and Midwives at the Cempaka Putih District Health Center. Data analysis using SPSS. In the results of this management, the data that has been obtained, the data is analyzed by presenting a Univariate table, in accordance with the variables studied so as to produce the distribution and presentation of each variable. Results: Based on the results of this study, it was shown that pregnant women who participated in pregnancy exercises at the Cempaka Putih District Health Center in 2017, with a population of all pregnant women as many as 1247 pregnant women, mothers who only participated in pregnancy exercises were 184 respondents (14.76%), while those who did not participate in pregnancy gymnastics were 1063 pregnant women (85.25%). Conclusion: Based on the results of this study, the description of pregnant women who participate in gymnastics at the Cempaka Putih District Health Center, it can be concluded that of the 1247 pregnant women who checked their pregnancy, only 184 respondents (14.76%) took part in pregnancy exercises, and those who routinely participated in pregnancy exercises only (27.2%). Keywords: Pregnant Women, Pregnancy Gymnastics,